Meningkatkan Aktivittas Dan Basil Belajar Siswa Melalui Pendekatan Pembelajaran Realistik Pada Siswa Kelas V SD INPRES Baliase Kecamatan Marawola Kabupaten Sigi - Erlinda Erlinda; Samsurizal N. Suleman; Solfarina Solfarina (Universitas Tadulako, 2015)
This study aimed to improving activity and learning outcomes of students at fifth grade SD Inpres Baliase, Sigi County through implementing realistic learning approach. Data was collected by instrument of rubric of lesson plan, activity observation sheets of students and teacher, and formative test. The result of study showed that realistic learning approach could be improved students activities and learning outcomes. The student activities in first and second cycles have good categories. The learning by realistic approach could to be improving students learning outcomes. That was known by compare classical absorption between before and after action research. The learning outcome of first cycle has increased, although less that indicators. In the second cycle, it had significant and reach the classicai absorption as a school settled. Improve activity and learning outcomes was consequence of realistic learning approach that was first cycle in good categories and second cycle in very good.